INTEGRATED MINERAL AND BIOSTIMULANT NUTRITION ENHANCES BASIL PRODUCTIVITY AND ESSENTIAL OIL COMPOSITION UNDER SEMI-ARID FIELD CONDITIONS IN IRAQ (European Science Methodical Journal, 2026)
Background: Sweet basil (Ocimum basilicum L.) is one of the most commercially valuable aromatic herbs in the world, but in Iraq the farm-level performance of the crop is regularly underperforming compared to what has been demonstrated by experimental plots to be possible in the country - a shortcoming that suggests that evidence-based guidelines on fertilisation should be developed to suit the local climate. Aim: The aim of the study was to determine whether NPK compound fertiliser (20:20:20) or humic acid, or the combination of the two, would have any significant effect on the vegetative development, leaf colour, herb yield and essential oil production of basil grown in semi-arid conditions in central Iraq. Methods: There were eight interventions in a randomised complete block design (three replicates), comprising unfertilised control, three NPK rates (50-150 kg ha -1), two foliar humic acid concentrations (1.5 and 3 g L -1) and two NPK-humic acid combinations. Measurements were made at the pre flowering stage. Findings: NPK alone at 100 kg ha -1 and humic acid alone at 3 g L -1 (T8) always performed better than others. There was a more than 2-fold increase in fresh aerial weight as compared to the control, an overall chlorophyll of 3.05 mg g -1 FW, and essential oil yield of 47.3 L ha -1. Profiling GC-MS revealed an increase in linalool of 41.3 in the control to 48.3 in T8 - an increase that boosts commercial oil value. Conclusion: It was found that combining moderate NPK with foliar humic acid was more effective than either treatment and the combination is suggested as a viable solution to fertilisation of basil growers in Salah al-Din and other semi-arid governorates in Iraq.